Pengaruh Kepribadian, Ekspektasi Pendapatan, dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha - Rohma Septiawati; Meliana Puspitasari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of personality, income expectations, and educational entrepreneurship on the Interest in Entrepreneurship of accounting students at Buana Perjuangan University, Karawang. This research includes comparative causal research. The population of this study were accounting students at Buana Perjuangan Karawang University class of 2019 with a total of 152 students. The data collection method in this study was to use a questionnaire or questionnaire given to the entire population. Instrument testing was carried out on accounting students at Buana Perjuangan Karawang University class of 2019 with a total of 152 students. The classic assumption test includes the normality test, linearity test, multicollinearity test, and heteroscedasticity test. The hypothesis test used is simple linear regression analysis and multiple linear regression. Keywords: HR, Income Expectations, Entrepreneurship Education, Interest in Entrepreneurship.